The Policies of the Presidents of the Audiencia of Panama against the Maroonage, 1600-1637 - Tardieu, Jean-Pierre (Revista Complutense de Historia de América, 2022)
After the defeat of the Maroon Kingdom of Bayano at the end of the 16th century, at the beginning of the 17th century the presidents of the Royal Audiencia of Panama continued fighting against maroonage, which never ceased to rise from its ashes. This threat was more pressing for the royal coffers than in other kingdoms of the Indies because of the fear aroused by the hypothetical alliances between maroons from different provinces along the Atlantic coast of the isthmus (from Acla to Cartagena de Indias) and the Angolan negroes from a stranded frigate on the same coast, with the indomitable Indians of Urabá. The presidents had to reduce the juridical and financial contradictions and dissensions on the part of the slaveowners, the oidores of the Audiencia and even the Crown.